Pengaruh Lingkungan Kerja Dan Komunikasi Terhadap Kinerja Karyawan Pada PT Kopedana Mitra Sekuritas BRI Danareksa Sekuritas Mitra Bekasi - Cindy Kartika Dewi; Hasanuddin (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2024)
This research aims to measure the influence of the work environment and communication on employee performance at PT Kopedana Mitra Sekuritas BRI Danareksa Sekuritas Mitra Bekasi. The population and sample used in this research used saturated samples. The data collection tool in this research used a questionnaire with 46 respondents. The design used in this research is testing using SPSS for Windows version 26. The results of this research show that: (1) Work Environment has a significant effect on Employee Performance, (2) Communication has a significant effect on Employee Performance, (3) Work Environment and Communication has a significant effect on Employee Performance of PT Kopedana Mitra Sekuritas. This research provides suggestions to PT Kopedana Mitra Sekuritas to pay more attention to the facilities in the work environment, and pay attention to the communication system that occurs between employees and colleagues and also to customers so that employee performance can improve.